PERLINDUNGAN HUKUM TERHADAP KONSUMEN DALAM PRAKTIK PINJAMAN ONLINE BERBASIS FINTECH DI INDONESIA: ANALISIS YURIDIS DAN EMPIRIS TERHADAP IMPLEMENTASI REGULASI PERLINDUNGAN KONSUMEN - Muhammad Dirga Satria Kurnianto; Trubus Rahardiansyah; Maya Indrasti Notoprayitno (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This study aims to analyze legal protection for consumers in the practice of online lending based on financial technology (fintech) in Indonesia through normative and empirical juridical approaches. The rise of consumer rights violations—such as misuse of personal data, abusive debt collection, and lack of transparency—reflects the weak enforcement of existing regulations, despite the issuance of several laws, including the Consumer Protection Law, the Electronic Information and Transactions Law (ITE), the Personal Data Protection Law (PDP), and relevant OJK regulations. This research outlines the forms of legal protection provided, including consumers' rights to clear information, data privacy safeguards, and dispute resolution mechanisms. In practice, however, supervision over illegal online lending remains inadequate, public legal literacy is low, and available complaint mechanisms are often ineffective. The study also reveals that although dispute resolution efforts through internal (IDR), external (LAPS), and litigation channels exist, structural and cultural barriers continue to place consumers in a disadvantaged position. Therefore, a reformulation of consumer protection policies that is more progressive, integrated, and justice-oriented is urgently needed. Strengthening inter-agency coordination, enforcing criminal sanctions for serious violations, and enhancing public digital and legal literacy are strategic steps toward realizing effective legal protection in Indonesia's rapidly evolving fintech lending ecosystem.